Digital Pedagogical Approach for Effective Teaching and Learning Process in Tertiary Education System in Nigeria (UNIZIK Journal of Educational Management and Policy, 2026)
Education system is continually witnessing pedagogical transformation in recent time. This paperthus delves into some concepts relating to effective adaptation of digital tools in teachinglearning process in the ever-evolving landscape of tertiary education in Nigeria. It posits thatdigital pedagogical skills are characterized by the ability to use and learn through ICTs in anacademic environment and highlights key ways in which digital tools enhance pedagogicalpractices in tertiary education. Obstacles to effective implementation of digital tools ineducational institutions such as inadequate funding, poor curriculum development, rapid pace oftechnological change, reluctance to change, insufficient professional development opportunities,among others, were identified. It concludes that effective application of digital tools in teachinghas the capacity to eliminate some barriers that lead to poor achievement and ineffectiveteaching-learning process. Adequate funding of tertiary institutions and investment in the latesttechnological tools are thus recommended, among others, to facilitate effective digital teachinglearning process in tertiary institutions in Nigeria.
Keywords: Teaching, digital pedagogy, learning process, tertiary, education.